The relationship between workplace empowerment and employee commitment among support staff of State Human Resource Unit in Wisma Bapa Malaysia, Kuching, Sarawak/ Nur Atiqah Rajali - Rajali, Nur Atiqah (2019)
The purpose of this study was to investigate the relationship between the relationship between workplace empowerment and employee commitment among support staff of State Human Resource Unit in Wisma Bapa Malaysia, Kuching, Sarawak. This study was conducted to examine the relationship of opportunity, resources, power and support towards employee commitment among support staff of State Human Resource Unit in Wisma Bapa Malaysia, Kuching, Sarawak. Besides that, to get the result for the study, the were 120 questionnaires distributed to the support staff s and only 101 questionnaires were returned and considered usable with response rate of 84%. Then, the data of the study were using Statistical Package for Social Science (SPSS) version 23.0 data file. The result of this study shows that Support has a strong, significant and positive relationship result with the Employee’s Commitment to the organization (r=.688, n=101, p<0.01). Besides that, the result between Power and Employees’ Commitment shows that it has a strong, significant and having positive relationship (r=.583, n=101, p<0.01). As for Resources, it shows a moderate, significant and positive relationship with Employees’ Commitment (r=.426, n=101, p<0.01). Lastly, for the Opportunity, the results show that it has a moderate, significant and positive relationship with Employees’ Commitment (r=.468, n=101, p<0.01). Apart from that, this study also has discussed the result of each of the research questioned and there were a few recommendations that can be applied for the organization, employees also for the future researchers.